Aplication of the mandibular canine index for the determintation of sex in patients of Lima – Peru using cone beam computed tomography - Llaguno Rubio, Jhoana Mercedes (2020)
Objective: To determine the association between the mandibular canine index (MCI) and sex by evaluating cone-beam computed tomographies (TCHC) of patients attending a radiographic center during 2014 to 2017. Methodology: 500 TCHCs of 184 men and 316 women ages 12-50 years were assessed using RealScan 2.0 software. The distal mesio diameter of the right and left lower canines was determined, as well as the lower intercanine distance in each TCHC. Then, the presence of sexual dimorphism was determined according to the canine teeth, with the left canine presenting the highest value (5.67%), and with these data, the MCI was obtained for each TCHC. Subsequently, the standard MCI cut-off point was determined, obtaining a value of 0.264 and the real value of the sex of each TCHC was compared with the cut-off point. Results: The efficacy of the MCI was 55.43% in men and 54.75% in women (kappa = 0.095). Conclusion: The MCI is not a good determinant for estimating sex.